Green computing approach to reduce power consumption - Kaur, Parminder (My University, 2015)
No doubt that the extensive use of computers and its devices has made our lives easy and comfortable but it has left an ever lasting impact on our environment. This techno-savvy world has led to increase in the huge amount of power consumption which further led to increase in the emission of green house gases like carbon-dioxide. Therefore, energy conservation and power management has become a critical issue of this modern world. And Green Computing addresses this problem of energy conservation by providing green solutions. Due to rising environmental concerns, the concept of green computing has been in much limelight. Green Computing is the buzzword of today’s IT world. It aims to reduce the use of hazardous material, maximize the energy efficiency and promote recyclability of the products. The problems of high power consumption, electronic waste (e-waste) management and energy efficiency has gained much more attention. But the need of saving the energy has become the top priority in the IT world and by implementing green practices these needs can be fulfilled. In this thesis, an approach for reducing the power consumption of a system had been proposed. This approach can be used to save the power and also help us to use our system and resources in an eco-friendly way. Approach is being supported by an algorithm, flowchart and sequence diagram and for implementing the algorithm CloudSim tool is used
ME-Computer Science-Thesis
Keywords: Cloud Computing; Green Computing; computer science; cse